3D SPH numerical simulation of the wave generated by the vajont rockslide - Vacondio, Renato; Pagani, Serena; Mignosa, Paolo; Genevois, Rinaldo (Italian journal of engineering geology and environment, 2013)
<span data-sheets-value="{"1":2,"2":"In this paper a 3D numerical modeling of the wave generated by the Vajont slide is presented. In order to completely describe the complex flow generated by the slide a Smoothed Particle Hydrodynamics (SPH) technique was adopted. To the best of the author knowledge this is the first attempt to describe the events adopting a fully 3D numerical model which discretizes the Navier-Stokes Equations. The SPH adopted herein is a meshless Lagrangian technique which is able to simulate the highly fragmented violent flows generated by the falling slide in the Vajont artificial reservoir. Moreover the Compute Unified Device Architecture (CUDA) of nVidia devices parallelization technique has been adopted to obtain the speed-up sufficient for the high resolution needed to accurately describe the phenomenon. The simulation results have been validated by comparing the maximum run-up and the water level in the residual lake after the events against the ones reported in literature. In addition to that, the 3D velocity field of the flow during the event together with the discharge hydrograph which overflowed the dam has been obtained."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">In this paper a 3D numerical modeling of the wave generated by the Vajont slide is presented. In order to completely describe the complex flow generated by the slide a Smoothed Particle Hydrodynamics (SPH) technique was adopted. To the best of the author knowledge this is the first attempt to describe the events adopting a fully 3D numerical model which discretizes the Navier-Stokes Equations. The SPH adopted herein is a meshless Lagrangian technique which is able to simulate the highly fragmented violent flows generated by the falling slide in the Vajont artificial reservoir. Moreover the Compute Unified Device Architecture (CUDA) of nVidia devices parallelization technique has been adopted to obtain the speed-up sufficient for the high resolution needed to accurately describe the phenomenon. The simulation results have been validated by comparing the maximum run-up and the water level in the residual lake after the events against the ones reported in literature. In addition to that, the 3D velocity field of the flow during the event together with the discharge hydrograph which overflowed the dam has been obtained.